Isolation and characterisation of an antifolate insensitive (afi1) mutant of Arabidopsis thaliana. (5th June 2012) - Navarrete, O.; Van Daele, J.; Stove, C.; Lambert, W.; Storozhenko, S.; Van Der Straeten, D.
Abstract: Antifolates can impair the synthesis and/or function of folates in living organisms. Mechanisms of resistance or tolerance to antifolates have been mainly described in plants using the drug methotrexate. In this work, the antifolate trimethoprim (TMP) was used with the aim of revealing a novel mechanism of resistance. EMS mutagenised seeds from Arabidopsis were screened to isolate individuals insensitive to TMP. Genetic analysis revealed a homozygous recessive mutation that segregates with the phenotype of tolerance to 50 μm TMP. Mapping analysis localised the mutation at the end of the short arm of chromosome 3. Preliminary characterisation demonstrated up‐regulation of several genes from the folate biosynthetic pathway in the TMP insensitive mutant, and a slight increase in total folate content in the mutant as compared with the Col‐0 control. Moreover, sequence analysis of the DHFR (dihydrofolate reductase) genes, which encode a known target for resistance to antifolates, did not reveal any changes. This study is the first report of a stable mutant insensitive ( afi1 ) to the antifolate trimethoprim in plants, and suggests the existence of a novel mechanism of resistance to antifolates.